Measuring Core Inflation in India - Abhiman Das, Joice John, Sanjay Singh (India Economic Review, 2009)
The inflation, which is, calculated as year-on-year percent change in general price level, is a combined effect of several types of price changes. The monetary authority tries to track that part of inflation, which can be effectively monitored and controlled using various monetary instruments. This persistent component of inflation is termed as Core Inflation, which comprises long-run properties as well as predictive power of future inflation. In this paper, 12 different measures of core inflation making use of 8 different methodologies viz. Exclusion basis, Mean-SD, Median, Trimmed Mean, Historical Standard Deviation, Hodrick-Prescott Filter, Wavelet Filter and Structural Vector Auto Regression (SVAR) are presented. Moreover, this paper has outlined 9 approaches for judging the preferred measure(s) based on different properties of core inflation.